Chapter Il corpus parallelo italiano-russo del NKRJa. Progetto di ampliamento, applicazioni e sviluppi - Biagini, Francesca (Biblioteca di Studi Slavistici, 2019)
With this article, we introduce our project for enlarging the Italian-Russian parallel corpus of the NKRJa (Nacional'nyj korpus russkogo jazyka) and outline several of its current and future applications. The newly expanded corpus has now reached roughly four million words, and we expect to reach 20 million, the size required for a corpus that is balanced and reliable. In order to illustrate possible applications for the Italian-Russian parallel corpus, we offer two examples: the first is its experimental use in the teaching of translation at the University of Bologna; the second its use in the context of research in Russian-Italian Contrastive Linguistics on the topic of the non-temporal qualities of the Russian future tense.